2020
DOI: 10.7717/peerj.10125
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus johnsonii BS15 improves intestinal environment against fluoride-induced memory impairment in mice—a study based on the gut–brain axis hypothesis

Abstract: Background Excessive fluoride can lead to chronic neurodegeneration characterized by neuron and myelin loss and memory dysfunction. The gut–brain axis hypothesis suggests that gut microbiota plays a crucial role in regulating brain function. Thus, using probiotics to adjust the gut microenvironment may be a potential therapy for mental diseases. Methods Mice in the prob group were administrated with Lactobacillus johnsonii BS15 for 28 days prior to and throughout a 70-day exposure to sodium fluoride. The dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 77 publications
(84 reference statements)
1
5
0
Order By: Relevance
“…Notably, the behavioral performance of mice with acute alcohol intake was significantly ameliorated by BS15 pretreatment; thus, the positive effects of L. johnsonii BS15 prove it as a potentially beneficial bacterium. The changes in the behavioral tests induced by L. johnsonii BS15 pretreatment were consistent with the conclusions of our earlier research (Sun et al, 2020;Xin et al, 2020;Wang et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Notably, the behavioral performance of mice with acute alcohol intake was significantly ameliorated by BS15 pretreatment; thus, the positive effects of L. johnsonii BS15 prove it as a potentially beneficial bacterium. The changes in the behavioral tests induced by L. johnsonii BS15 pretreatment were consistent with the conclusions of our earlier research (Sun et al, 2020;Xin et al, 2020;Wang et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…Our study also verified the preventative influence of L. johnsonii BS15 on drunkenness. The normal animal memory level relies upon a delicate change in the intestinal flora, organizational barrier, and circulation system (Sun et al, 2020;Xin et al, 2020Xin et al, , 2021aWang et al, 2021). Although various factors, such as neuroinflammation, lipid peroxidation, autophagy, and apoptosis, can affect brain health, the gut microbiome plays a significant role as one of the main drivers.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, L. johnsonii BS15 can attenuate inflammation in obese mice (Xin et al, 2014 ); L. johnsonii La1 can be useful in preventing bacterial translocation in cirrhosis (Soriano et al, 2012 ). L. johnsonii BS15 intake benefits the neuroinflammation and demyelination in the hippocampus (Xin et al, 2020 ). Similarly, we observed that L. johnsonii decreased the level of inflammatory factors in an LPS‐induced sepsis mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…All animals were fed standard food in the laboratory, and the laboratory temperature was set to 21-24°C, the humidity to 50 ± 5%, and the light and dark cycle to 12 h. After one week of adaptation, the mice were randomly divided into ve groups: a control group (C), uorosis group (F), sodium butyrate group (S), uorosis and 500 mg/kg sodium butyrate treatment group (F + S1), and uorosis and 1000 mg/kg sodium butyrate treatment group (F + S2), with 10 mice in each group. According to the previous literature, 100mg/L sodium uoride can cause brain damage in mice [9,31,32]. Except for groups C and S, all groups were provided with distilled water containing 100 mg/L uoride (Sigma-Aldrich, St. Louis, MO, USA).…”
Section: Animals and Treatmentmentioning
confidence: 99%